Implementasi Metode Smart (Simple Multi Atribute Rating Technique) Dalam Menentukan Jurusan Di Sma Hkbp 2 Tarutung - Selly Marselina Hutabarat (Cattleya Darmaya Fortuna, 2021)
Wrong One role of SPK in the field of education is in the decision-making process for the selection of majors in high school, which in nature can assist decision makers in providing alternative decisions for appropriate majors for students, where the results of the decisions can be used as material to assist teachers and students in making decisions. Most students only follow friends to follow friends to choose a major so that it allows students to feel unsuitable after entering the major. Therefore we need a decision support system that can calculate the value, ability and personality of students to help determine majors in high school. Smart is a multi-criteria decision-making method developed by Edward in 1977. This multi-criteria decision-making technique is based on the theory that each alternative consists of a number of criteria that have values and each criterion has a weight that describes how important it is compared to other criteria. The author uses this method to make it easier to determine the right major, according to the desired criteria. This problem can be classified into problems that are multi-objective (many goals to be achieved) and multi-criteria (many criteria that determine in reaching the decision). The author uses this method to make it easier to determine the right major, according to the desired criteria. This problem can be classified into problems that are multi-objective (many goals to be achieved) and multi-criteria (many criteria that determine in reaching the decision). The author uses this method to make it easier to determine the right major, according to the desired criteria. This problem can be classified into problems that are multi-objective (many goals to be achieved) and multi-criteria (many criteria that determine in reaching the decision).